Pembangunan Olahraga Ditinjau Dari Sport Development Index : Aspek Partisipasi Dan Kebugaran Jasmani Masyarakat Guna Peningkatan Kualitas Pendidikan Jasmani Di Kota Magelang (Universitas Negeri Semarang, 2020)
The research objective is to study the value of the index of community sports participation and physical fitness of the community in the City of Magelang in terms of the Sports Development Index. The method used in this research is quantitative. The research locations are in the District of North Magelang, District of South Magelang, and District of Central Magelang. Data collection instruments by means of observation, interviews, questionnaires, documentation, and the Multistage Fitness Test (MFT). Data collection on population in the city of Magelang more than 7 years with a total of 90 people, sports participation and physical fitness of the community. The city of Magelang was 0.0212324 and the physical achievement index in the city of Magelang was 0.2283, with the results of the index values of both aspects of the City of Magelang in terms of the Sports Development Index in the low category.